Olsztyńskie badania emigrantologiczne. Historia – stan obecny – perspektywy rozwoju - Ndiaye, Iwona Anna (Acta Polono-Ruthenica, 2019)
Olsztyn is an important center of emigrant-related research in Poland. The first works in this field were written at the beginning of the 1990s century. Currently, the results of research concerning the history of emigration literature are presented in the scientific series “The Luminaries of Russian Emigration”, “Theory and Practice of Translation”, “Between Words – Between the Worlds” and the scientific journal “Acta Polono-Ruthenica”.In 2018, at the Institute of Eastern Slavic Studies, UWM initiated a statutory subject Emigran-tion studies. Interpretation – Reception – Translation, which aims at conducting research focused on the description of history and heritage issues of cultural Russian emigration that can be assigned to such thematic areas as: history of the Russian literary process, issues of interpretation of the lit-erary text, Polish-Russian literary relations and literary translation. The essential focus the team is interdisciplinary research. The subject of the team’s research focuses on the most important aspects of emigration-related research, including the history of emigration, fate, the status of the emigrants and their spiritual, religious and political life.The author discusses the history, current state and perspective of Olsztyn’s emigration research, with particular emphasis on their international dimension.